Neuroinflammatory Gene Expression Pattern Is Similar between Allergic Rhinitis and Atopic Dermatitis but Distinct from Atopic Asthma - Sobkowiak, Paulina (Biomed Res Int, 2020)
METHODS: In the study, we included 86 children diagnosed with atopic asthma (n = 25), allergic rhinitis (n = 20), and atopic dermatitis (n = 20) and healthy control subjects (n = 21) of Caucasian origin from the Polish population. The blood leukocyte expression of 31 genes involved in neuroinflammatory response (neurotrophins, their receptors, neuropeptides, and histamine signaling pathway) was analysed using TaqMan low-density arrays. The relative expression of selected proteins from plasma was done using TaqMan Protein Assays. Statistical analysis was done using Statistica. RESULTS: Blood expression of 31 genes related to neuroimmune interactions showed significant increase in both allergic diseases, allergic rhinitis and atopic dermatitis, in comparison to the control group. We found 12 genes significantly increased in allergic rhinitis and 9 genes in which the expression was elevated in atopic dermatitis. Moreover, 9 genes with changed expression in atopic dermatitis overlapped with those in allergic rhinitis. Atopic asthma showed 5 genes with altered expression. The peripheral expression of neuroinflammatory genes in the human study was verified in target tissues (nasal epithelium and skin) in a rat model of allergic inflammation. CONCLUSIONS: A common pattern of neuroinflammatory gene expression between allergic rhinitis and atopic dermatitis may reflect similar changes in sensory nerve function during chronic allergic inflammation.